2020
DOI: 10.3390/ijms21030979
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics for Metabolic Diagnostic Screening with Automated Data Interpretation Using a Knowledge-Based Algorithm

Abstract: M.vanderHam-3@umcutrecht.nl (M.v.d.H.); B.Prinsen@umcutrecht.nl (H.C.M.T.P.); M.H.Broeks-3@umcutrecht.nl (M.H.B.); M.G.deSain@umcutrecht.nl (M.G.M.d.S.-v.d.V.); N.Verhoeven@umcutrecht.nl (N.M.V.-D.)Abstract: Untargeted metabolomics may become a standard approach to address diagnostic requests, but, at present, data interpretation is very labor-intensive. To facilitate its implementation in metabolic diagnostic screening, we developed a method for automated data interpretation that preselects the most likely in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
(38 reference statements)
0
20
0
Order By: Relevance
“…The most favorable biochemical stringency of the paired Z-score threshold turned out to be <−3.0 and >3.0. Interestingly, this paired Z-score threshold is more stringent than often used for NGMS [8,11,12,14], although for most diagnostic metabolites in IEMs, Z-scores are >3.0 [8,[10][11][12][13][14]. As is true for the maximum distance to the primary reaction, the most favorable paired Z-score threshold may also vary for the different IEMs [14], as some IEMs may present with more subtle metabolic aberrations than others [8,[10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most favorable biochemical stringency of the paired Z-score threshold turned out to be <−3.0 and >3.0. Interestingly, this paired Z-score threshold is more stringent than often used for NGMS [8,11,12,14], although for most diagnostic metabolites in IEMs, Z-scores are >3.0 [8,[10][11][12][13][14]. As is true for the maximum distance to the primary reaction, the most favorable paired Z-score threshold may also vary for the different IEMs [14], as some IEMs may present with more subtle metabolic aberrations than others [8,[10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of NGS as a first-tier diagnostic tool has greatly increased the diagnostic yield and reduced diagnostic delay, which are both important benefits for patients [16][17][18]. Although the implementation of NGMS in clinical diagnostics is in its infancy when compared to NGS, several recent studies reported its potential applicability in clinical diagnostics of IEMs for individual patients [8][9][10][11][12][13][14]. Notwithstanding its added value, NGMS is-unlike NGS-not expected to become a stand-alone diagnostic tool, as genetic confirmation of the resulting diagnosis is often required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have implemented an ultra‐high performance liquid chromatography‐quadrupole time‐of‐flight mass spectrometry (UHPLC‐QTOF‐MS) method for fast and accurate quantitative detection of 71 metabolites, replacing GC‐MS for the analysis of organic acids 4 . This was already promising in the light of metabolomics literature 5,6 since we obtained explicit biochemical signatures for 16 of the 18 organic acidurias included in the clinical validation.…”
Section: Introductionmentioning
confidence: 99%
“…inborn errors of metabolism (IEM) (Kerkhofs, et al, 2020) (Alaimo, et al, 2020) (Linck, et al, 2020). Some strategies have already been developed for this purpose; Haijes et al applied expert knowledge to develop an algorithm that matches metabolic signatures obtained from metabolomics with expected metabolic signatures caused by each IEM, thereby ranking potential enzymatic deficiencies (Haijes, et al, 2020). Similarly, Baumgartner et al explored the use of classification algorithms to distinguish multiple IEM based on differences in metabolite levels (Baumgartner, et al, 2004).…”
Section: Introductionmentioning
confidence: 99%